Nitrous Oxide Emissions Estimated With the CarbonTracker‐Lagrange North American Regional Inversion Framework. Issue 3 (23rd March 2018) - Nevison, Cynthia; Andrews, Arlyn; Thoning, Kirk; Dlugokencky, Ed; Sweeney, Colm; Miller, Scot; Saikawa, Eri; Benmergui, Joshua; Fischer, Marc; Mountain, Marikate; Nehrkorn, Thomas
Abstract: North American nitrous oxide (N2 O) emissions of 1.6 ± 0.3 Tg N/yr over 2008–2014 are estimated using the CarbonTracker‐Lagrange regional inversion framework. The estimated N2 O emissions are largely consistent with the EDGAR (Emission Database for Global Atmospheric Research) global inventory and with the results of global atmospheric inversions but offer more spatial and temporal detail over North America. Emissions are strongest from the Midwestern Corn/Soybean Belt, which accounts for nearly one third of the total North American N2 O source. The emissions are maximum in spring/early summer, consistent with a nitrogen fertilizer‐driven source, and also show a late winter spike suggestive of freeze‐thaw effects. Interannual variability in emissions across the primary months of fertilizer application is positively correlated to mean precipitation. The estimated N2 O flux from the Midwestern Corn/Soybean Belt and the more northerly United States/Canadian wheat belt corresponds to 4.2–4.6% and 2.2–3.0%, respectively, of total synthetic + organic N fertilizer applied to those regions. Consideration of nonagricultural sources and additional N inputs from soybean N2 fixation could reduce the N2 O yield from the Midwestern Corn/Soybean Belt to 2.2–2.4% of total N inputs. Plain Language Summary: Emissions of nitrous oxide (N2 O) emissions over North America were estimated based on an inverse model, in which atmospheric concentrations of N2 O measured at 40 different National Oceanographic Atmospheric Administration (NOAA) sites were "inverted" to estimate surface sources. The estimated N2 O emissions showed a clear hot spot in the Midwestern corn/soybean belt, which accounted for nearly one third (0.48 ± 0.02 × 10 12 g N/yr) of the total North American N2 O source (1.6 ± 0.3 × 10 12 g N/yr). The emissions were maximum in spring and early summer, consistent with the timing of nitrogen fertilizer application to the corn/soybean belt. Interannual variability across 2007–2015 in the inferred emissions suggested that climate may interact with fertilizer to influence N2 O source strength, with the warm drought year 2012 showing substantially lower emissions than other years. Key Points: The Midwestern Corn/Soybean Belt is a hot spot for N2 O emissions and accounts for 30% of total emissions from North America Half of annual N2 O emissions from this belt occurs between April and July, corresponding to the time of spring N fertilizer application About 2.2‐2.4% of N inputs to the corn/soybean belt, including soybean N2 fixation and synthetic and organic N fertilizer, are emitted as N2 O